IMPLEMENTASI KEBIJAKAN SERTIFIKASI GURU SEKOLAH DASAR DI KABUPATEN SUMEDANG - Indra Wahyudinata; Abdul Jalil; Daffa Nugraha; Racka Nandra Gumilar; Rafli Fathurrohman (JRPA - Journal of Regional Public Administration, 2023)
Education is the most important aspect in efforts to optimize human resource services, in order to be able to compete amidst the competencies of an increasingly advanced and modern nation. Sumedang Regency Education Office by optimizing education services through implementing the teacher certification policy regulated in Permendiknas No. 11 of 2011 concerning in-service teacher certification and the latest Regulation of the Minister of Education and Culture No. 37 of 2017 concerning certification for teachers in positions which aims to increase teacher professionalism in carrying out their duties and functions.The aims of this study were 1) to examine and describe the implementation of the primary school teacher certification policy at the Sumedang District Education Office, in terms of communication, resources, position, and organizational structure. 2) To find out the efforts made by the Sumedang district education office to overcome the teacher's ability to use IT.This research is a qualitative type using a phenomenological approach. with data collection techniques through structured interviews, observation and documentation. The results of the study show that 1) of the four aspects of communication, resources, disposition and organizational structure, the fourth shows that the implementation has been well implemented, so that overall the implementation of the primary school teacher certification policy in Sumedang district is considered to have gone well. 2) the determinant factors supporting the success of the primary school teacher certification policy in Sumedang district which are considered well implemented due to organizational structure factors that have occurred a good division of tasks and the existence of procedural operational standards (SOP) or technical certification manuals. Apart from that, another supporting factor is the aspect of communication carried out through various socialization activities. 3) Efforts by the education office to overcome teachers' abilities in using IT, namely through technical guidance activities (BIMTEK) related to offline and online based teacher certification implementation systems.